Challenges of pricing luxury in commercial aviation – will first class disappear?. Issue 4 (17th August 2018) - Oancea, Octavian
Abstract Nowadays, in the era of commoditization of commercial aviation, airlines' efforts to restore profitability seem to translate more than ever with a focus on economy class. Many new aircraft are ordered with high-density configurations, and the existing ones are sometimes reconfigured to offer more economy seats, either by reducing the space occupied by those seats, or by shrinking the capacity of the other cabins. Is there still any first class demand and how does it differ from the business class demand? What is luxury in commercial aviation? In this paper, we address the role of the first class cabin in commercial aviation, the challenges of pricing luxury and whether first class still has a future in the years to come versus private aviation.